HIGH SCHOOL STUDENTS’ AND UNIVERSITY UNDERGRADUATES’ CAREER PLANNING ABILITIES AND THEIR RELATION TO TIME PERSPECTIVE - Kairys, Antanas; Urbanavičiūtė, Ieva; Pociūtė, Birutė; Liniauskaitė, Audronė (Acta Paedagogica Vilnensia, 2013)
Vocational choice, including career planning and decision-making, depends on numerous factors. It has been proven that while abilities, interests, and values are important in this process, it is also essential to examine how a person sees his or her past experience, present situation, and future goals or expectations. It is thought that the so-called time perspective might play a significant role in career planning, because it relates to strategies that are employed when making decisions.While many young people have quite a clear vision of their future and are able to adequately “connect” the past, the present, and the future, the opposite also exists, often leading to negative consequences. For example, holding to the “living now and here” principle relates to a less thoughtful planning which, in turn, might lead to poor career decisions. Studies on time perspective and career planning are not very frequent; however, an in-depth exploration of these variables might provide a valuable insight into the process of career choice.This study was aimed to explore student career planning in different time perspective clusters. In total, 379 respondents participated in the study (203 high school students and 176 university undergraduates). Two career planning variables reflecting the perceived career planning abilities were measured in the study: 1) career adaptabilities were measured in the high school students’ subsample and 2) career decision self-efficacy was measured in the undergraduates subsample. All respondents were asked to fill out a self-report questionnaire comprised of career adaptabilities / career decision self-efficacy and time perspective scales.The results have revealed five time perspective clusters that encompass five different time perspectives and reflect a pattern in a person’s relation to time (such as “positive-experience-oriented”, “extremely future-oriented”, “neutral”, etc.). Referring to the cluster composition, statistically significant gender differences were found in the high school students’ subsample only. In the students’ subsample, gender distribution did not differ significantly across clusters. Moreover, statistically significant differences were found regarding career adaptabilities in the high school students’ subsample, those in the “positive-experience-oriented” and “extremely future-oriented” clusters demonstrating significantly higher career adaptability scores. Considerably less differences in career decision self-efficacy were found across the clusters in the undergraduate subsample. According to the results, only self-appraisal and goal selection self-efficacy seem to be higher among the respondents that fall into the “extremely future-oriented” and “neutral” clusters.
Keywords: time perspective; career adaptabilities; career decision self-efficacy